Enterovirus Replication Organelles and Inhibitors of Their Formation - Li, Xinhong; Wang, Mingshu; Cheng, Anchun; Wen, Xingjian; Ou, Xumin; Mao, Sai; Gao, Qun; Sun, Di; Jia, Renyong; Yang, Qiao; Wu, Ying; Zhu, Dekang; et al. (Frontiers in Microbiology, 2020)
Enteroviral replication reorganizes the cellular membrane. In a concerted fashion, viral proteins and host factors generate unique organelle-like structures called replication organelles (ROs) to replicate their viral genomes. ROs promote efficient viral genome replication, allow spatiotemporal coordination of the steps of the viral replication cycle, and protect viral RNA from host immune responses. Combined use of ultrastructural and functional research has greatly increased our understanding of the architecture and biogenesis of ROs. Here, we review the recent findings concerning the role, architecture, biogenesis, formation mechanism, and inhibitors of enterovirus ROs.